Transkulturai Nilai Satlogi sebagai Pilar dalam Membangun Pendidikan Inklusif - Ahmad Fauzi; Ainol (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
This study aims to interpret and interpret the value of the satlogy of santri, which is believed and interpreted as a social magnet so that it can influence individual social behavior and actions, thus the value above is a social capital for pesantren in building an inclusive Islamic education paradigm. Inclusive Islamic education is basically a holistic expression of the struggles and clashes of local wisdom built on the basis of the Qur'an and al-Hadith. Thus, observing the condition of Islamic education in Indonesia for its various problems and challenges of course requires a new breakthrough in building a more open or inclusive Islamic education, by making the local wisdom of the santri satlogy as the main force to build and influence individual social thought and action, so that it can produce graduates who are competent. have an open mind, be able to respect differences and create social harmonization, in accordance with social conditions and national identity, by prioritizing mutual respect for differences, maintaining harmony in life based on the value system, as a reference as well as the main controller and mind-set of Islamic education future.